Diretrizes para avaliação de ruído de tráfego rodoviário visando a elaboração de mapas de ruído - Meller, Gabriela (2023)
The development of cities and the growth of motorized vehicles have increased urban noise significantly. Given this, assessing noise levels in urban environments and implementing appropriate noise control measures are important. The noise map is a useful tool in this process, which cartographically represents noise distribution in a specific area over some time. Some countries do not have a local noise prediction model, which makes it difficult to standardize the elaboration of noise maps. Thus, this study aims to propose guidelines for performing noise mapping in different land uses and occupations for Brazilian cities since there is no standardized Brazilian model. To this end, road traffic data, sound levels, physical-environmental conditions, and noise map simulations were measured, collected, and analyzed using SoundPLAN. It is also part of the methodological procedure of this research to identify, select, evaluate, and synthesize information, through a systematic literature review, on the use of different noise prediction models in countries that do not have a local model. The papers compiled by the systematic literature review showed that the most used traffic noise prediction models were RLS-90 and NMPB, and the most used mapping software were SoundPLAN and ArcGIS. Most measurements were carried out over 15 min at a ground level height of 1.5 m. The measurements and simulations in Santa Maria/RS showed that the RLS-90 model provided greater accuracy. For arterial, collector, and local roads, it was identified that the vehicular counting time can be the same as the sound level measurement time, except for local roads with heavy vehicle traffic. In situations involving gradient roads and traffic lights, it is necessary to perform measurements with a duration time equal to or longer than the vehicular deceleration point. Regarding optimizing the noise measurement time depending on the distance from the crossroad, it was found that for asphalt pavements, measurements can be performed with 10 min to 20 min duration for distances of 40 m, for locations with predominantly residential and commercial zoning, respectively. For concrete block pavements, it is recommended to perform sound measurements with a duration of 30 min for distances above 10 m. For gradient roads, it is recommended to measure sound levels at locations of vehicular acceleration on asphalt pavements, regardless of land use and coverage. For gradient roads with interlocking concrete blocks, the highest sound pressure level measurements tend to occur at the highest total vehicle flow location. For different distances from a crossroad, it is indicated to perform sound measurements at distances greater than 40 m, regardless of land use, occupation, and the type of road surface. As a result, this study aims to contribute to the standardization of noise mapping for different urban scenarios, providing essential data for urban planning to improve the population's quality of life.